The distribution of soil nitrifiers and efficacy of 3, 4-dimethylpyrazole phosphate changes with soil depth and calcium carbonate application. (November 2020) - Kaveney, Brooke; Condon, Jason; Doran, Gregory; Galea, Francesca; Rigg, Jessica
Abstract: The nitrification inhibitor 3, 4-dimethylpyrazole phosphate (DMPP) is used to limit nitrogen (N) losses incurred following nitrification of applied N fertilisers. Inhibitor efficacy changes with soil conditions including pH and organic matter (OM) content, both of which can be stratified down the soil profile. An incubation study was conducted using acidic soil that exhibited pH stratification. Soil samples were collected from the field in 2 cm depth increments to a depth of 10 cm. Two liming treatments were applied to each depth where the pHCa was raised above 6 or left in its initial acidic state. Nitrogen treatments (urea ammonium nitrate (UAN) with and without DMPP) were applied to each liming treatment per depth and incubated for four weeks. Destructive sampling for mineral N, DMPP concentration and pH occurred every week. The abundance of nitrifiers was determined using semi-quantitative real-time polymerise chain reaction (PCR) targeting the amoA gene at weeks 0, 1 and 4. Liming significantly increased nitrification rates and bacterial amoA gene abundance. Results showed the top 0–2 cm recorded the largest population of bacterial nitrifiers. Changes in pH influenced the composition of nitrifiers present in the soil. Bacterial nitrifiers were absent from the 8–10 cm soil layer in unlimed soils (pHCa 4.25) but liming caused an increase in gene abundance. Archaeal amoA gene abundance was highest in unlimed plots at 4–8 cm depth although populations decreased over the incubation period and also with lime application. DMPP effectively inhibited nitrification in limed plots, however no significant difference existed between UAN and DMPP treatments for unlimed treatments. DMPP successfully decreased bacterial amoA gene abundance in all depths that were limed but not in unlimed soils. Decreases in inhibitor concentrations occurred within one week in the 0–2 cm layer possibly due to bacterial decomposition associated with greater OM concentration at the soil surface. This study highlighted that DMPP use is more effective in relatively neutral soils and liming will change the abundance and distribution of nitrifiers within the top 10 cm of soil. Highlights: Liming significantly improved DMPP efficacy. Nitrification rates increase with liming. Highest DMPP efficacy occurred in layers below 4 cm for limed soils. AOB amoA abundance decreases with soil depth. AOB amoA gene copies only present at 8–10 cm in limed soils.